Expression of truncated chalcone synthase from Boesenbergia rotunda L. mansf. in Escherichia coli - Parmin, Nor Azizah (2013)
Chalcone synthase (CHS) is an entrance enzyme in the biosynthetic pathway of different flavonoids compound and become a critical regulatory enzyme. Truncated CHS was isolated from Boesenbergia rotunda (B. rotunda), also known as Chinese ginger, which is a medicinal and culinary herb from China and Southeast Asia. The popularity of its medicinal usage has drawn the attention of scientists to investigate on its medicinal properties. This research is a fundamentals works to study on the mechanism of truncated CHS from B. rotunda in E. coli. This study is new for this plant but CHS has been studied by many researchers in other plants. Optimization of B. rotunda specific CTAB RNA extraction method developed in this study was able to produce high yield of RNA with minimum polysaccharide contamination. The value of RNA yield for optimization of B. rotunda specific CTAB RNA extraction method was 2.0 μg/g. A reverse transcriptase-polymerase chain reaction (RT-PCR) based approach was used to identify and isolate a partial-length cDNA coding for CHS gene. The gene encoding truncated CHS from B. rotunda was cloned into pTrcHis2 expression vector and placed under the control of the trc promoter for high level expression in E. coli. The effect of inducer concentration and induction time on CHS production from inducible system was evaluated. The recombinant truncated CHS protein was characterized and optimized for higher expression. The optimization of the recombinant truncated CHS production of inducible system in 50 ml culture was done for the best clone truncated CHS from E.coli TOP10. The effect of IPTG concentration and induction time on truncated CHS production from inducible system was evaluated. A time course profile of recombinant truncated CHS production with the optimized condition was performed and produced after 16 h of induction time from recombinant truncated CHS5, while optimal IPTG concentration was 0.5 mM. The recombinant truncated CHS was purified by using affinity chromatography and Ion-Exchange Chromatography (IEX). The expressed CHS protein had a molecular weight of about 21 kDa, a size that matched with the prediction by bioinformatic analysis. Truncated CHS was highly active at 40oC, pH 8.0 with a half-life of 1 h 10 min at 30oC. 3D structure of truncated CHS from B. rotunda was predicted using CHS from alfalfa (Medicago sativa) as a template with sequence identity 74.87%. Tyr-42, His-130 and Asp-163 were assigned as catalytic triad residues. Truncated CHS was evaluated with Ramachandran plot, Verify 3D and ERRAT to validate the structure. This study may provide useful information on this enzyme and its function in the flavonoids biosynthetic pathway in B. rotunda that offers significant pharmaceutical properties for human health.